The rural homeless in Bangladesh - Rahman, Tahmeena, 1958-; UNICEF; Northern Ireland Federation of Housing Associations (Dhaka, Bangladesh : UNICEF, 1993)
Study restricted to four districts of Bangladesh and was conducted in 1987 and updated to 1991.
"The study of 'The rural homeless in Bangladesh' was funded by Northern Ireland Federation of Housing Associations, U.K. and also funded and published by United Nations International Children Emergency Fund (UNICEF)"--T.p. verso.
Includes bibliographical references (p. 104-105).
Maher
Keywords: Rural homeless person -- Bangladesh; Rural poor -- Bangladesh